2013
DOI: 10.1016/j.bpj.2013.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Conformational Heterogeneity of the AXH Domain of Ataxin-1: An Unusual Example of a Chameleon Fold

Abstract: Ataxin-1 is a human protein responsible for spinocerebellar ataxia type 1, a hereditary disease associated with protein aggregation and misfolding. Essential for ataxin-1 aggregation is the anomalous expansion of a polyglutamine tract near the protein N-terminus, but the sequence-wise distant AXH domain modulates and contributes to the process. The AXH domain is also involved in the nonpathologic functions of the protein, including a variety of intermolecular interactions with other cellular partners. The doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(84 citation statements)
references
References 33 publications
17
67
0
Order By: Relevance
“…Using a combination of NMR, analytical ultracentrifugation, X-ray and small angle scattering, we have previously shown that the observed behaviour is consistent with the presence of a monomer-dimer-tetramer equilibrium over a wide range of concentrations as well as with conformational heterogeneity of the different protomers [20]. When we titrated the 15 N-labelled AXH with unlabelled L-CICp, the NMR spectrum underwent a dramatic change ( Figure 2A , bottom ).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Using a combination of NMR, analytical ultracentrifugation, X-ray and small angle scattering, we have previously shown that the observed behaviour is consistent with the presence of a monomer-dimer-tetramer equilibrium over a wide range of concentrations as well as with conformational heterogeneity of the different protomers [20]. When we titrated the 15 N-labelled AXH with unlabelled L-CICp, the NMR spectrum underwent a dramatic change ( Figure 2A , bottom ).…”
Section: Resultssupporting
confidence: 64%
“…It is clear from these plots that the AXH structure is overall rigid with the exception of the AXH N-terminal tail and sparse residues located in short loop regions. Horizontal straight lines indicate the equivalent average values observed in isolated AXH [20]. C) Size exclusion chromatography study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AXH domain is known as a dimerization domain and is the only globular dimer forming region identified in the protein [92]. Additionally, the AXH folds independently into an oligonucleotide-binding fold, able to recognise RNA with a similar nucleotide preference, to that of full length ataxin-1 [91,93].…”
Section: Wild-type and Mutant Proteinmentioning
confidence: 99%
“…The increased polyQ stretch not only increases the tendency to aggregate, but also leads to conformational changes of other regions and domains of the SCA proteins. In the case of SCA1, conformational changes to the AXH domain, along with its ability to fold leads to the potential contribution of misfolded protein aggregation [92,98,99].…”
Section: Wild-type and Mutant Proteinmentioning
confidence: 99%